Pengembangan Media Pembelajaran Berupa Pop-up Book Pada Pembelajaran Bahasa Indonesia Kelas Tinggi di SDN 107430 Galang - Riris Nurkholida Rambe; Tiara Paramita Purba; Nur Arifa Hasanah; Aulia Khairani; Muhammad Fiqri Alwi; Aulia Rahman (Universitas 45 Surabaya, 2023)
This research is motivated by the problems found at SDN 107430 Galang, namely learning media that are not yet varied, as well as the limitations of tools and materials in the learning process. From the existing problems, pop-up book learning media was developed with the aim of (1) producing learning media in the form of pop-up books for Indonesian language learning class IV at SDN 107430 Galang (2) knowing students' responses to pop-up book learning media provided by the researcher. our research method. In this study we used a qualitative descriptive method. This type of qualitative descriptive research is a research method that utilizes qualitative data and is described in descriptive history. This type of qualitative descriptive research is often used to analyze events, phenomena, or situations socially.